ENVIRONMENTALLY FRIENDLY CONCRETE USING WASTE GLASS POWDER (WGP) AS A PARTIAL SUBSTITUTE OF CEMENT - Olii, Muhammad Ramdhan; Sahrul Hidayat, Andi; Saliko, Maxidin; Santoso, Triyadi; Hippy, Mohamad Alfandi; Pakaya, Ririn (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2023)
The utilization of waste materials in concrete production is gaining significant attention as a means to mitigate environmental issues and promote sustainable construction practices. This study investigates the potential of waste glass powder (WGP) as a partial replacement for cement in concrete. The aim is to evaluate the effects of WGP on the properties and performance of concrete, with a focus on enhancing sustainability and reducing the environmental impact associated with cement production. The experimental investigation involved preparing concrete mixtures with varying proportions of WGP, ranging from 10% to 25%, as a partial replacement for cement. Based on the research findings, it can be concluded that the substitution of 20%WGP) for cement is the optimal dosage. The results of various tests and evaluations show that the concrete has desirable properties and performance characteristics at this level of replacement. This 20% substitution ratio strikes a balance between maintaining adequate compresive strength and improving the concrete's sustainability. In conclusion, the incorporation of WGP as a partial replacement for cement in concrete shows promises as an environmentally friendly and sustainable approach. Further research and optimization of mix proportions are recommended to maximize the benefits of utilizing WGP in concrete and promote its widespread application in the construction industry.